(untitled) (gjstudies, 2025)
This research investigates the transformative impact of digital accounting system adoption onorganizational reporting structures, moving beyond traditional efficiency metrics to examinefundamental shifts in information architecture, decision-making processes, and stakeholdercommunication paradigms. While prior literature predominantly focuses on cost-benefit analysis and implementation challenges of technologies like Enterprise Resource Planning (ERP)systems, this study introduces a novel conceptual framework—the Tripartite Reporting Transformation Model (TRTM). This model posits that digital adoption catalyzes three concurrent,interdependent transformations: epistemological (changing the nature of financial knowledge),structural (reconfiguring data flows and reporting hierarchies), and teleological (redefining thepurpose and audience of reports). The methodology employs a longitudinal, multi-case studydesign across four diverse industries (manufacturing, healthcare, non-profit, and professionalservices), combining archival analysis of reporting artifacts pre- and post-digital adoption within-depth, semi-structured interviews with accounting personnel, operational managers, andC-suite executives. Findings reveal that digital adoption does not merely automate existingprocesses but often triggers a recursive re-imagination of what constitutes a ’report,’ leading tothe emergence of hybrid analytical narratives, real-time predictive dashboards, and externallyfacing integrated reports that blend financial and non-financial data. A significant and originalfinding is the phenomenon of ’reporting drift,’ where the formal, accounting-centric reportingsystem spawns informal, agile reporting sub-systems tailored for specific managerial needs,creating a dual reporting ecology. The study concludes that the organizational reporting transformation is a sociotechnical evolution with profound implications for accounting professionalism, data governance, and the strategic role of the finance function. The contribution is areframing of digital accounting adoption from a technological upgrade to a catalyst for epistemological and organizational change.